Star Wars storyboards the original trilogy - Rinzler, J. W. (Abrams, 2014)
"For the first time, Lucasfilm has opened its archives to present the complete storyboards for the original Star Wars trilogy--the world-changing A New Hope and its operatic sequels, The Empire Strikes Back and Return of the Jedi--as well as never-before-published art from early conceptual and deleted scenes"--Book jacket.